Współczesny styl życia przyczyną zachowań ryzykownych, w tym zażywania środków psychoaktywnych – na przykładzie NSP - Nosko , Damian (Studia Edukacyjne, 2023)
The article addresses one of the most difficult problems to solve at present, i.e. addiction and its causes. The author, Dr Damian Nosko, draws a close parallel between addiction to psychoactive substances and young people’s sense of insurmountable deficits. This most often results from a perceived clash, difficult to rationalize and often impossible to name, between expectations and authentic possibilities for realizing dreams and achieving goals. The essence of the reflections concerns an area related to engaging in risky behaviors, including reaching for psychoactive drugs as an outlet for emotions, forgetting about problems, and a substitute for pursuing real fulfilment. While the author ascribes a huge role in shaping socially desirable attitudes of youth during adolescence to family, they admit that the pace of life, consumerism, dependence on technological achievements and on mass media, as well as a lack of conclusive legal regulations do not facilitate the struggle for the well-being of young people and create a convenient possibility of raising a next generation of unfulfilled adults who are also predisposed to addictions.